Antimalarial activity of extracts of Malaysian medicinal plants - Rahman, N.N.N.A.; Furuta, T.; Kojima, S.; Takane, K.; Ali Mohd, M. (1999)
In vitro and in vivo studies revealed that Malaysian medicinal plants, Piper sarmentosum, Andrographis paniculata and Tinospora crispa produced considerable antimalarial effects. Chloroform extract in vitro did show better effect than the methanol extract. The chloroform extract showed complete parasite growth inhibition as low as 0.05 mg/ml drug dose within 24 h incubation period (Andrographis paniculata) as compared to methanol extract of drug dose of 2.5 mg/ml but under incubation time of 48 h of the same plant spesies. In vivo activity of Andrographis paniculata also demonstrated higher antimalarial effect than other two plant species. (C) 1999 Published by Elsevier Science Ireland Ltd. All rights reserved.